The Relationship Between Physical Activity, Sleep Behaviors, and Gastrointestinal Symptoms During COVID-19. (7th June 2021) - Evenson, Alexa; Wachowiak, Jena
Abstract: Objectives: To determine the relationships between physical activity, sleep behaviors, and gastrointestinal (GI) symptoms during the current COVID-19 pandemic in college students. Methods: College students ( n  = 459; aged 18–23) at a midwestern university participated in the study. Participants completed an online survey in mid-April 2020, which included the International Physical Activity Questionnaire-Short Form and amended versions of the Pittsburgh Sleep Quality Index (PSQI) and Gastrointestinal Symptoms Questionnaires. Spearman rho correlation coefficients were used to analyze the data. Results: Higher GI mean total scores were significantly related to higher vigorous and moderate intensity physical activity total minutes for the overall sample (rs = 0.112, P < 0.05); and for participants identifying as female (rs = 0.134, P < 0.05). Higher GI mean total scores were significantly related to longer sleep duration for the overall sample (rs = 0.111, P < 0.05) and for participants identifying as male (rs = 0.258, P < 0.01). In males, longer sleep duration was also significantly related to a decrease in sleep quality (rs = –.226, P < 0.05). Conclusions: The findings reveal a positive correlation between GI symptoms and vigorous and moderate-intensity activity. Moreover, GI symptoms were related to longer duration but decreased quality of sleep. Healthcare professionals and college campus resources could focus on promoting lower intensity exercise and improved sleep behaviors to decrease GI symptoms. Funding Sources: None.